The Antimicrobial in Vitro Effects of Different Concentrations of Some Plant Extracts Including Tamarisk, March, Acetone and Mango Kernel - Ziba Shabani and Ahmad Sayadi (Journal of Applied Pharmaceutical Science, 2014)
The present study was aimed to assess the plants antimicrobial effects such as Tamarisk, March, acetone and mango kernel. The aqueous and ethanol extract of the plants and also its smoke was prepared in concentrations of 50 and 25 mg/mL. The bacteria Staphylococcus aureus, Streptococcus pyogenes, Streptococcus pneumoniae, Pseudomonas aeruginosa, Candida albicans, Enterococcus faecalis were cultured by linear method. Impregnated extract discs were seeded onto the medium and the diameter of inhibition zone was measured following incubated for 24 h. The mango kernel extract by ethanol showed maximum inhibition zone diameter. Despite the weak antibacterial effect of aqueous and ethanol extract of Tamarix, Smoke extract of this plant shows good antimicrobial properties. Different extracts of March showed antimicrobial effects only on Candida albicans. Aqueous and ethanol extracts of acetone did not show significant effects.
Keywords: Antibiogram,aqueous extract,ethanol extract,smoke extract,acetone,March,Tamarisk,mango kernel.